ASSESSING THE COMMUNITY PRACTICES AND PERCEPTIONS ON WASTE SORTING IN URBAN INDONESIA: A CASE STUDY IN GORONTALO CITY - Sri Maryati; Budiyanto Ahaliki; Rahmat Taufik R.L Bau; Hermila A; Adnan Engelen; Gita Juniarti; Indrawan Indrawan (USN Kolaka, 2025)
This study examines the practices and perceptions of urban residents regarding household waste sorting in Gorontalo City, Indonesia. This study involved 400 household respondents, covering eight sub-districts and 50 urban villages within Gorontalo City. Five key dimensions were assessed including knowledge of environmental and economic benefits, individual motivation, preferences for sorting incentives, perceived difficulty, and actual sorting habits. Data were analyzed using descriptive quantitative techniques with tabulation and percentage analysis. The findings reveal that 73.75% of respondents are aware of the benefits of waste sorting. However, only 32.75% are motivated by environmental awareness, while others are constrained by limited facilities or habitual barriers. Incentive preferences show that 41.25% of respondents favor financial compensation, while 42% prefer improved access to sorting infrastructure. In terms of perceived difficulty, 48.5% consider waste sorting easy, but 37.5% find it moderately difficult and 14% perceive it as difficult. Ultimately, only 12.75% of respondents consistently sort their waste, 39.75% do so occasionally, and 47.5% never engage in sorting. These findings highlight a significant knowledge action gap and underscore the need for integrated policy strategies that combine education, infrastructure development, and incentive-based community engagement to foster sustainable household waste sorting behavior.